Increased levels of high sensitive Troponin-T after first dose of Adriamycin containing therapy may predict brain-type natriuretic rise after 6 months in patients with breast carcinoma - Şahin, Osman; Çağlayan, Çağlar Emre; Celik, Aziz İnan and Matyar, Selcuk and Cureoglu, Asligul and Karaaslan, Muhammet Buğra and Demirtas, Mustafa and Paydas, Semra (Scientific Reports in Medicine, 2026)
Objective: In this study, we aimed to investigate the usefulness of highly sensitive troponin-T (hs-TnT) levels for the early prediction of anthracycline-related cardiac stress and subclinical cardiac dysfunction. Method: Patients newly diagnosed with breast cancer with normal cardiac function were randomized to our study. All patients had taken 240 mg/m2 adriamycin in 12 weeks. Brain-type natriuretic peptide (BNP) and hs-TnT levels were measured; echocardiography and tissue Doppler imaging was performed to all patients for 4 times: at baseline, 4-12 hours after first adriamycin dose, at 3 months and at 6 months. Results: A total of 43 women (52.7±12.1 years) with breast cancer were included in our study. Brain natriuretic peptide elevation was observed in 8 patients, in which 2 of them showed symptoms and signs of overt heart failure. In the logistic regression analysis, hs-TnT levels (OR: 1.154; (0.974–1.336 in 95% CI) and BNP levels (OR: 1.009 (1.001-1.018 in 95 % CI) measured 12–24 hours after first adriamycin dose were independently associated with BNP rise at 6th month. Receiver operating curve analysis revealed a cut-off value of 12.85 ng/L for hs-TnT levels to predict BNP elevation at 6th month with 62.5% sensitivity and 85.7% specificity. Conclusion: hs-TnT levels after first dose of adriamycin containing therapy higher than 18.65 ng/L was associated with BNP elevation at 6th month with a specificity of 97.1% in our patient group. Early hs-TnT elevation may represent a potential marker of chemotherapy-related cardiac dysfunction.